Balloon Pulmonary Angioplasty: State of the Art - John G Coghlan (Radcliffe Medical Media, 2021)
Balloon pulmonary angioplasty (BPA) is a novel technique for the treatment of chronic thromboembolic pulmonary hypertension. While cardiologists need no introduction to the concept of balloon angioplasty, BPA has its own particular challenges. This article aims to provide the reader with an overview of BPA, starting with an introduction to chronic thromboembolic disease (CTED), the standard management of chronic thromboembolic pulmonary hypertension (CTEPH), technical challenges faced when performing BPA and the evidence base supporting its use. The second part of the article will focus on the future of BPA, in particular the areas where research is required to establish an evidence base to justify the role of BPA in CTEPH and CTED treatment.